Serum SALL4 Is a Novel Prognosis Biomarker with Tumor Recurrence and Poor Survival of Patients in Hepatocellular Carcinoma. (17th April 2014) - Han, Su-xia; Wang, Jun-lan; Guo, Xi-jing; He, Chen-chen; Ying, Xia; Ma, Jin-lu; Zhang, Yuan-yuan; Zhao, Qian; Zhu, Qing
Abstract : Aim . Sal-like protein 4 (SALL4), is reexpressed in tissues of a subgroup of HCC associated with poor prognosis. Reports of SALL4 serological levels linked to HCC patients are meager and unclear in the prognosis of this malignancy. Methods . Immunohistochemistry and optical microscopy protocols were used to examine the presence of SALL4 in liver tissues from the following patients: 38 HCC, 11 chronic hepatitis B virus (HBV), 13 liver cirrhosis, and 12 healthy controls. Additionally, enzyme-linked immunosorbent assay (ELISA) was used to measure the SALL4 levels in serum samples isolated from patients as follows: 127 with HCC, 27 with HBV, 24 with liver cirrhosis, and 23 normal controls. Results . Analysis of liver tissues sections from HCC patients (18 out 38; 47.4%) showed positive staining for SALL4 and its expression did no correlate with any of the clinicopathologic characteristics. HCC patients displayed higher levels (50.4%) of SALL4 protein in serum, compared with the three control groups. Moreover, SALL4 concentration reached the maximum level after one week after treatment and dropped quickly after one month. These HCC patients showing high SALL4 serum levels had poor prognosis, evidenced by both tumor recurrence and overall survival rate. Conclusions . High SALL4 serum levels are a novel biomarker in the prognosis of HCC patients.